Effect of Mucuna pruriens Seed Extract Pretreatment on the responses of spontaneously beating Rat Atria and Aortic Ring to Naja sputatrix (Javan Spitting Cobra) Venom - Fung, Shin Yee; Tan, Nget Hong; Sim, Si Mui; Aguiyi, John C. (Hindawi, 2012)
Mucuna pruriens Linn. (velvet bean) has been used by native Nigerians as a prophylactic for snakebite. Rats pretreated with M. pruriens seed extract (MPE) have been shown to protect against the lethal and cardiovascular depressant effects of Naja sputatrix (Javan spitting cobra) venoms, and the protective effect involved immunological neutralization of the venom toxins. To investigate further the mechanism of the protective effect of MPE pretreatment against cobra venom toxicity, the actions of Naja sputatrix venom on spontaneously beating rat atria and aortic rings isolated from both MPE pretreated and untreated rats were studied. Our results showed that the MPE pretreatment conferred protection against cobra venom-induced depression of atrial contractility and atrial rate in the isolated atrial preparations, but it had no effect on the venom-induced contractile response of aortic ring preparation. These observations suggested that the protective effect of MPE pretreatment against cobra venom toxicity involves a direct protective action of MPE on the heart function, in addition to the known immunological neutralization mechanism, and that the protective effect does not involve action on blood vessel contraction. The results also suggest that M. pruriens seed may contain novel cardioprotective agent with potential therapeutic value.